Faktor-Faktor yang Memengaruhi Foerign Direct Investment (FDI) di Enam Koridor Ekonomi Indonesia: Market Seeking atau Resource Seeking? - Iriani Trisna Rahayu; Ernawati Pasaribu (Jurnal Aplikasi Statistika & Komputasi Statistik, 2017)
The economic development of a country depends on the amount of foreign direct investment (FDI), including in the Indonesian six economic corridors. The huge gaps of conditions in economic corridors are expected to differences infactors affecting the FDI-inflow into the corridors. This study uses a panel data regression to analyze factors behind the FDI-inflow in each economic corridor and to determine the FDI characteristic in each economic corridor. It shows that the proportion of government capital expenditure, number of highly-educated labor force, trade openness, and the proportion of oil and mineral export affect the FDI-inflow only in some economic corridors. Furthermore, it indicates that, while market seeking FDI occurred in all Indonesian economic corridors, resource seeking FDI was only found in Sulawesi, Maluku and Papua economic corridors.